Natural Resources Management in African Agriculture: Understanding and Improving Current Practices 2002
DOI: 10.1079/9780851995847.0065
|View full text |Cite
|
Sign up to set email alerts
|

Farmers as co-developers and adopters of green-manure cover crops in West and Central Africa.

Abstract: This paper refers to 4 technologies involving cover crops and integrated crop-livestock interventions developed in West and Central Africa under varying social, ecological and production systems, in which farmers and researchers, working in partnership to combine indigenous knowledge and circumstances with research interventions, have contributed to the development of the final innovation. The 4 technologies are: improved Mucuna fallows; crop-livestock production in dry savannas; Stylosanthes as a feed and fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[4] reported that food-forage crops integration with different methods (nonconventional forage production systems) are important and appropriate in areas where the land shortage is a problem and the agricultural production system is subsistence. Cereal based cropping system through different methods is one of the strategic interventions for optimizing the productivity of a given land use system [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…[4] reported that food-forage crops integration with different methods (nonconventional forage production systems) are important and appropriate in areas where the land shortage is a problem and the agricultural production system is subsistence. Cereal based cropping system through different methods is one of the strategic interventions for optimizing the productivity of a given land use system [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Opportunity costs can be high in terms of labor when the timing of operations coincides with other vital activities and in terms of land when increased organic nutrient production means taking more valuable land out of production (see Omiti et al, 1999 andWilliams, 1999 for animal manure). Recent research has uncovered numerous farmer innovations to reduce labor and land inputs (Waddington, 1999;Tarawali et al, 2002;Misiko and Ramisch, unpublished data).…”
Section: Actual Nutrient Management Practices Of African Farmersmentioning
confidence: 99%
“…Development of such skills could be achieved through providing environmental education (in the local language) and farmer-training programmes. Raising the farmers' awareness of the benefits of new technologies and conservation measures would be important because farmers are unlikely to adopt a new technology if they do not perceive its immediate benefits (Demeke, 2003;FAO, 2012b;Tarawali et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The present study adopts a participatory approach to landscape performance assessment (Ecoagriculture Partners, 2012;Willemen et al, 2014) and engages the local communities' and other key stakeholders' perceptions of the sufficiency of local resources and their effectiveness in promoting livelihoods. Research has shown that participation results in greater adoption and use of proposed technologies (Demeke, 2003;Tarawali et al, 2002). As such, participatory approaches are widely used by conservation proponents.…”
Section: Conceptual Frameworkmentioning
confidence: 99%